2018
DOI: 10.3390/ijms19102871
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis: Path and Progression to Significance

Abstract: This paper tells the story of how hormesis became recognized as a fundamental concept in biology, affecting toxicology, microbiology, medicine, public health, agriculture, and all areas related to enhancing biological performance. This paper assesses how hormesis enhances resilience to normal aging and protects against a broad spectrum of neurodegenerative, cardiovascular, and other diseases, as well as trauma and other threats to health and well-being. This paper also explains the application of hormesis to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
138
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 70 publications
(104 reference statements)
3
138
2
1
Order By: Relevance
“…One possible explanation is that higher concentrations of EtBr may have triggered a defense mechanism, such as efflux of EtBr or upregulated DNA repair pathways, that may explain the lower number of canavanine-resistant colonies. Such an explanation would be consistent with hormesis [36,37]. Nonetheless, the number of canavanine-resistant colonies from yeast grown in EtBr from 0.1 to 10 μg EtBr/L was significantly more than control ( Fig 2B ), demonstrating that we could detect the mutagenic potential of yeast even at concentrations lower than the limit of detection for the Ames test.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…One possible explanation is that higher concentrations of EtBr may have triggered a defense mechanism, such as efflux of EtBr or upregulated DNA repair pathways, that may explain the lower number of canavanine-resistant colonies. Such an explanation would be consistent with hormesis [36,37]. Nonetheless, the number of canavanine-resistant colonies from yeast grown in EtBr from 0.1 to 10 μg EtBr/L was significantly more than control ( Fig 2B ), demonstrating that we could detect the mutagenic potential of yeast even at concentrations lower than the limit of detection for the Ames test.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, we observed that the lower concentrations of EtBr (0.1 and 1.0 μg EtBr/L) produced higher numbers of canavanine-resistant colonies than the highest concentration of EtBr (10 μg EtBr/L), a biphasic response consistent with hormesis. Briefly, hormesis is when a low dose of a toxin produces a higher effect than a lower dose, perhaps because the higher dose induces protective responses not triggered by the lower dose [36,37]. This observation was reproducible in two more independent runs of the parallel chemostats (S1 C and D Figs ).…”
Section: Resultsmentioning
confidence: 75%
“…It is possible that CXA‐10, like many signaling agents, exhibits hormesis (inverted U‐shaped dose response curve), which has been observed with CXA‐10 in animal models . Inverted U‐shaped dose response curves are common with drugs that regulate signaling pathways and may protect against overexposure by simply “turning off” functions at high concentrations …”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic application of ncRNAs cannot be conceived otherwise than by using ultra-low doses in the context of a nanotherapy as currently represented by the BI(G)MED. This is made possible by the principle of Hormesis, borrowed from toxicology, and applied to nanodoses, which explains the rule of reversal of action according to the dose (Figure 12) [28,29].…”
Section: Resultsmentioning
confidence: 99%